Reclaiming the Landbodymind Erotic: Queer First Nations “Storytelling Wholeness” and “Some Properly Hot Gay Sex” - Han Reardon-Smith (Journal of Global Indigeneity, 2023)
This paper explores a series of recent works of speculative fiction and poetry by queer First Nations writers—including Ellen van Neerven, Laniyuk, Alison Whittaker, SJ Norman, and Jazz Money—to touch on the depth and breadth of Blak Queer embodiment, erotics, joy, and imagination. The focus is on reading these texts vulnerably, with an ethic of companion-thinking in respect to Indigenous Standpoint Theory, attentive to my relationality and responsibilities as a queer white colonial-settler situated on stolen Aboriginal Land. Thinking in company with queer First Nations creative writing and erotics in this way redefines the horizon of possibility in imagining a world beyond what Wiradjuri transgender/non-binary scholar and artist Sandy O’Sullivan (2021 p.1) calls “the colonial project of gender (and everything else).”